A Spatial Domain Approach of Fingerprinting for Colored Digital Images (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper, a spatial domain approach of fingerprinting is presented for colored digital images. A semi-blind fingerprinting conveys a secure arrangement for trading of digital images. The operational significance of the digital fingerprinting system is verified and estimated. Digital fingerprint implanted doesn’t disturb the perceptible feature of the host digital image. Multi-user collusion attacks are prevented using the proposed apparoach. Variable fingerprint size and dissimilar location insertion play significant role for inhibiting attack.